Metal-Free Addition of Boronic Acids to Silylnitronates - Kerim, Mansour Dolé; Boyode, Pakoupati; Garrec, Julian; El Kaïm, Laurent (Synlett, 2020)
We report for the first time a metal-free addition of boronic acids to silylnitronates to afford oxime derivatives through aryl transfer on the carbon nitrogen double bond. A reaction mechanism has been proposed in relation with a DFT study on the key aryl transfer. This arylation process is effective for cycloalkenyl nitro derivatives leading to oximes that may be oxidatively converted into 3-arylisoxazole derivatives.
Keywords: nitro; silyl nitronate; boronic acid; oxime; isoxazole